PELATIHAN E-COMMERCE PADA PRODUK OLAHAN IKAN DI RUMAH PRODUKSI KRUPUK JAMILA - Ristyanadi, Bhiaztika; Rahmat Saleh, Fuquh; Nur Azizah, Luluk (Jurnal Pengabdian Kepada Masyarakat (MEDITEG), 2024)
As times change, corporate players must broaden the marketing network for the goods they manufacture. One of them is the presence of e-commerce, which is growing more and more common as marketplace services become more accessible. encouraging corporate players to focus more on the visual appeal of their products, such as by using packaging that appeals to consumers, in addition to their quality. The ease of transaction services, which eliminate the need for in-person meetings, is next. Another strategy that works well to draw in customers is offering discounts as part of a campaign. At the Jamila cracker production facility, this activity offers e-commerce training together with socialisation. execution of the strategies created during counselling for the creation of Shopee accounts for online sales. The issue that partners are facing is that social media is not being used to its full potential as a marketing and sales tool. The service implementation team suggested alternate alternatives, such as hosting Shopee e-commerce outreach and training for Jamila cracker product sales, to address these partner issues and promote Jamila cracker product sales.